Teknologi Sebagai Pendekatan Dalam Optimalisasi Pendidikan Agama Islam (PAI) - Barkati, Ahmad; Cahyadi, Ani (Jurnal Pendidikan Agama Islam, 2024)
This research is aimed at optimizing technology in Islamic religious education. Islamic religious education must be able to keep pace with technological developments. Apart from that, the teacher as a learning resource and facilitator must be able to manage the technology facilitated by the school, technology as an approach so that teachers are able to simplify and optimize lesson time for students. The target to be achieved in this research is that teachers are able to use technology as optimally as possible. The research method used is library research, namely research carried out using literature (libraries), whether in the form of books, notes, or reports of research results from previous researchers. The data collection technique used in this article is documentation, namely a technique data collection by searching for documents related to the research problem. These documents can be books, images, previous articles, and others. The results of this research explain several important things which are concepts that must be understood by teaching staff, such as Online Learning, Virtual Reality (VR), Augmented Reality (AR), Artificial Intelligence (AI), Gamification, Mobile Learning, Cloud Computing, Big Data , Internet of Things (IOT) andnLearning Analytics. In order to improve the quality of learning, teachers are expected to be able to operate the technology controlled and facilitated by the school.